THE RELATIONSHIP OF LANDEK KARO TRADITIONAL DANCE AND THE CHARACTER EDUCATION OF CHILDREN IN SIOSAR VILLAGE KABUPATEN KARO - Fanesa Anastasya Br Depari; Rumiris Lumbangao; Ribka Kariani Br Sembiring; Darinda Sofia Tanjung (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to assess and determine the relationship between the Landek Karo traditional dance and character education among children aged 9 to 13 years in the relocation area of Mount Sinabung, Siosar Village, Pertibi Lama, Kecamatan Merek, Kabupaten Karo, North Sumatra. The population of this research consisted of 156 children aged 9 to 13 years in Siosar Village. The samples were selected through purposive sampling; in this case, the researcher chose 35 children aged 9 to 13 years who were dancers in the Siosar Festival event held in September 2019 in Siosar Village. This research employed a quantitative survey method, which aimed to analyze the research results using t-test hypothesis testing. The findings indicated that the average t-count score for the Landek Karo traditional dance was 24.843, which was greater than the t-table value of 1.683 and categorized as high. Similarly, the average t-count score for character education was 24.843, which was also greater than the t-table value of 1.683 and categorized as high. Therefore, Ho was accepted, indicating that there was a relationship between the Landek Karo traditional dance and the character education of children in Siosar Village, Kabupaten Karo.